READINESS OF ORANG ASLI COMMUNITIES IN ROYAL BELUM-TEMENGOR FOREST COMPLEX, PERAK TOWARDS SUSTAINABLE ECO-CULTURE TOURISM (ECT) PROGRAMME - Kamarudin, Khairul Hisyam; Ngah, Ibrahim; Abd Wahid, Siti Nurhuda; Razak, Khamarrul Azahari (Journal of Human Capital Development (JHCD), 2015)
The study develops a new instrument in measuring the validity of the questionnaire in technology banking applications using the Rasch model as an alternative method. Usually, classical method, the Cronbach alpha (α), is used to prove the validity of the instrument. In addition, the Rasch measurement model is also capable of providing guidance to proof quality items to strengthen the legitimacy of the survey instrument. Questionnaire consisting of 28 items and using a 5-level Likert scale with very unimportant to very important as the form of semantic differential was distributed to 223 respondents. Bond and Fox software analysis showed different response patterns to construct items that were measured in the same logit. Findings show the more widespread application of Rasch models would lead to a stronger justification of measurement particularly in cross-cultural studies and whenever measures of individual respondents are of interest. Keywords: sustainable eco-cultural tourism, Royal Belum-Temengor, Orang Asli, forest complex, biodiversity